CONSIDERATIONS ON WOMEN’S NEEDS FOR DAYLIGHT IN CONTEMPORARY RESIDENTIAL ARCHITECTURE - Shatwan, Alaa (PEOPLE: International Journal of Social Sciences, 2018)
Humans share common needs and rights; however, there are special needs which vary according to gender. Women in Saudi Arabia spend long periods of time at home and are responsible for domestic duties. This creates particular needs for women which for men are easily fulfilled in the outside world, such as exposure to daylight. Furthermore, privacy has been studied as a major concern for Muslims and Arabs in their homes, and a number of studies have discussed window design and privacy culture in the vernacular architecture of different Muslim countries. Yet little attention is given to the point of how privacy effects daylight level in contemporary homes, where glass windows are the major source daylight and ventilation. This contributes to figuring out factors affecting daylight level according to each case variation. Therefore, this study aims to find out if women mandatory right of daylight is sufficiently considered inside homes by studying daylight level during daytime in Jeddah city. This research studies daylight lux level in twelve modern flats in Jeddah. Diva for Rhinoceros is the tool to figure out the accurate daylight in different daytime of different seasons. Finding reported that the amount of daylight that enter all examined living rooms are less than the required level. The paper concludes that there is major lack of daylight in most examined flats due to different factors such as glass type, exterior obstruction, and window size.